Women's Language in The Ellen DeGeneres Show on CBS TV Channel - Alda Faradiba Syah (ELITE: Journal of English Language and Literature, 2016)
This research is intended to analyze how Women’s Language is described by inThe Ellen DeGeneres Show based on Lakoff’s perspective. The result shows that Women’s Language feature by Lakoff is used by Ellen and her guest, Meghan Trainor in Ellen DeGeneres Show talkshow to express their feelings as a woman. This research shows that the women’s language in Ellen DeGeneres Show affects how women deliver their speech between the conversations, their feelings are expressed using the feature of women’s language clearly. Out of 10 feature of Women’s Language based on Lakoff’s perspective, the researcher found 7 feature among which the feature that appear the most is lexical hedges or filler with 6 data which implicated as the way women change the topic, convey uncertainty and prolonged speech. Ellen using lexical hedges or filler to make their conversation and changing the topic smoothly. Whereas Meghan Trainor using fillers to convey uncertainty in their conversation.